Implementasi Kebijakan Blue Economy dalam Pemberdayaan Masyarakat di Pantai Wini, Kecamatan Insana Utara, Kabupaten Timor Tengah Utara - Vinsensius Naikteas; Fransina W. Ballo; Cicilia A. Tungga (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the implementation of Blue Economy policies in Wini Beach, North Insana District, North Central Timor Regency, focusing on the empowerment of coastal communities. Using a qualitative approach, this study analyzes marine potential, the implementation of conservation areas, and the economic and social impacts of Blue Economy. The results indicate that this approach, which includes sustainable fishing practices, ecotourism development, and technical training, has improved the income and well-being of coastal communities. The introduced fishermen's training program successfully introduced environmentally friendly fishing techniques, while ecotourism promotion attracted tourists and created new job opportunities. However, challenges such as the lack of facilities, funding, and technical knowledge still persist. This study recommends enhancing collaboration between the government, NGOs, and local communities to address these challenges. In the three villages (Wini, Oesoko, Oekolo), the findings show that Blue Economy effectively enhances community welfare and environmental sustainability. However, challenges such as the lack of technical knowledge and infrastructure remain obstacles. Recommendations include increased training, infrastructure support, and regular evaluations to ensure long-term sustainability.